Stereotactic ablative radiotherapy for early stage non-small cell lung cancer: A critical literature review of predictive factors of relapse. (November 2016) - Loganadane, Gokoulakrichenane; Martinetti, Florent; Mercier, Olaf; Krhili, Samar; Riet, François-Georges; Mbagui, Rodrigue; To, Hanh; Le Péchoux, Cécile; Levy, Antonin
Highlights: SABR has become a standard treatment for early stage non-operable NSCLC. Predictive factors (PF) have been extensively described in surgical patients. Knowing such PF for SABR patients could lead increasing outcomes and building future trials. Abstract: Stereotactic ablative radiation therapy (SABR) has become the standard treatment for peripheral medically non-operable patients with early stage non-small cell lung cancer (NSCLC). Previous attempts of trials to compare SABR and surgery have failed and new randomized studies (SABRtooth, STABLEMATES, and VALOR) are ongoing. While predictive factors of relapse have been extensively studied in patients receiving surgery, there is scarce data on such putative factors in SABR patients. The purpose of this review is to analyze such predictive factors through a critical review of the literature.